2021
DOI: 10.1523/eneuro.0002-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Phenotype and Underlying Cellular Defects inDrosophilaKnock-In Models of DS (R1648C) and GEFS+ (R1648H)SCN1AEpilepsy

Abstract: Seizure phenotype and underlying cellular defects in Drosophila knock-in models of DS (R1648C) and GEFS+ (R1648H) SCN1A epilepsy ABSTRACT Mutations in the voltage-gated sodium channel gene SCN1A are associated with human epilepsy disorders, but how most of these mutations alter channel properties and result in seizures is unknown. This study focuses on two different mutations occurring at one position within SCN1A. R1648C is associated with the severe disorder Dravet Syndrome, and R1648H, with the milder disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Furthermore, a hyperpolarized deactivation threshold in para R-C and para R-H sodium currents was observed, which was present at both room temperature and elevated temperature. Taken together, the similar results from behavioral and electrophysiological studies indicate that the different phenotypes observed in humans may be mainly due to differences in genetic background rather than distinct changes in sodium channel function ( Roemmich et al, 2021 ).…”
Section: Drosophila In Epilepsy Researchmentioning
confidence: 74%
See 3 more Smart Citations
“…Furthermore, a hyperpolarized deactivation threshold in para R-C and para R-H sodium currents was observed, which was present at both room temperature and elevated temperature. Taken together, the similar results from behavioral and electrophysiological studies indicate that the different phenotypes observed in humans may be mainly due to differences in genetic background rather than distinct changes in sodium channel function ( Roemmich et al, 2021 ).…”
Section: Drosophila In Epilepsy Researchmentioning
confidence: 74%
“…Seizures are often refractory to treatment and patients display several other clinical features, such as cognitive, behavioral, and motor impairments ( Mei et al, 2019 ; Zuberi et al, 2022 ). To investigate the underlying disease mechanisms of these both disorders, several GEFS+ and DS mutations have been knocked into the orthologous Drosophila gene para at corresponding positions ( Sun et al, 2012 ; Schutte et al, 2014 ; Roemmich et al, 2021 ). The first variant to be explored was the GEFS+ mutation K1270T in the transmembrane segment 2 of homology domain III ( Sun et al, 2012 ).…”
Section: Drosophila In Epilepsy Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutation was thought to affect protein function by the bioinformatics tools. For patients with genetic epilepsy, the connection between a specific mutation and their behavioral symptoms is largely unknown (11). To clarify the relationship between the KCNAB3 gene mutation (H258R) and GEFS+, wild and mutant plasmids were constructed and transfected into human embryonic kidney 293 (HEK293) cells for patchclamp detection.…”
Section: Introductionmentioning
confidence: 99%